A New Synthesized Schiff Base as Corrosion Inhibitor for Mild Steel in a HCl Medium: Experimental, Density Functional Theory and Molecular Dynamics Simulation Studies - Kaabi,Ilhem (2021)
Abstract A new inhibitor Schiff base ether ligand, L1, di[(4-phenylamino)2,4-dihydroxy salicylaldehyde], was synthesized and characterized using mass spectra, elemental analysis, IR spectra, UV-Vis spectra, 1H NMR spectroscopy and thermal analysis. Electrochemical properties were investigated using cyclic Voltammetry (CV). The corrosion inhibition effect of the new prepared Schiff base was examined on mild steel (X48) in a 1 M HCl solution, by using gravimetric and electrochemical measurements. The potentiodynamic polarization results showed that the investigated Schiff base acted as a mixed kind inhibitor (cathodic/anodic), with some cathodic predominance. The adsorption procedure on X48 surface obeyed Langmuir isotherm. The associated adsorption activation factors and thermodynamic parameters were evaluated and interpreted. The inhibitor layer formed on the metal surface was characterized by AFM and SEM. The solid-state molecular geometry has been studied with the theoretical data obtained by density functional theory (DFT). Furthermore, the interaction between the inhibitor and Fe (1 1 0) surface was achieved by molecular dynamics simulations.